Natural Honey- as an Effective Adjunct in the Management of Radiation Induced Oral Mucositis - Karthikeya Patil; M S Vishveshwara; Mahima V Guledgud; Aishwarya R; Prasannasrinivas Deshpande; Nagabhushana Doggalli (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background - Malignancies are second most common cause of death in the world. Betel quid chewing,smoking, alcohol and low socioeconomic status contribute to its high prevalence. Its treatment protocolincludes surgery, radiotherapy, chemotherapy or a combination. Oral mucositis is an unavoidable mostfrequent, painful, distressing clinical side effect of radiotherapy.Methods – The study group consisted of 102 subjects diagnosed with carcinoma of head and neck andplanned for radiotherapy and had developed oral mucositis, among which 51 were in control group and 51in interventional group. The control group received 0.9% normal saline while interventional group receivednatural honey as topical application. Both the groups were evaluated by World Health Organization oralmucositis assessment scale and symptoms were assessed on verbal basis at baseline (I visit) and along withfour follow-up visits at an interval of 10 days, for total period of 40 days by 2 investigators. The studyduration was of 2 years.Conclusion- This study concludes that the topical application of honey can be used as an adjunct inalleviating the symptoms and in effective management of radiation mucositis as it is an easily available,simple, potent and inexpensive agent.